Multimodel Surface Temperature Responses to Removal of U.S. Sulfur Dioxide Emissions. Issue 5 (14th March 2018) - Conley, A. J.; Westervelt, D. M.; Lamarque, J.‐F.; Fiore, A. M.; Shindell, D.; Correa, G.; Faluvegi, G.; Horowitz, L. W.
Abstract: Three Earth System models are used to derive surface temperature responses to removal of U.S. anthropogenic SO2 emissions. Using multicentury perturbation runs with and without U.S. anthropogenic SO2 emissions, the local and remote surface temperature changes are estimated. In spite of a temperature drift in the control and large internal variability, 200 year simulations yield statistically significant regional surface temperature responses to the removal of U.S. SO2 emissions. Both local and remote surface temperature changes occur in all models, and the patterns of changes are similar between models for northern hemisphere land regions. We find a global average temperature sensitivity to U.S. SO2 emissions of 0.0055 K per Tg(SO2 ) per year with a range of (0.0036, 0.0078). We examine global and regional responses in SO4 burdens, aerosol optical depths (AODs), and effective radiative forcing (ERF). While changes in AOD and ERF are concentrated near the source region (United States), the temperature response is spread over the northern hemisphere with amplification of the temperature increase toward the Arctic. In all models, we find a significant response of dust concentrations, which affects the AOD but has no obvious effect on surface temperature. Temperature sensitivity to the ERF of U.S. SO2 emissions is found to differ from the models' sensitivity to radiative forcing of doubled CO2 . Plain Language Summary: We find that U.S. sulfur dioxide emissions influence temperatures in both the United States and in remote regions of the world. Three diverse climate models, all of which include the interaction of chemistry with the Earth system, produce similar northern hemisphere temperature responses. This is important because, while the emissions, atmospheric composition, and radiative forcing are most clearly expressed in the United States, the temperature changes are present over most of the northern hemisphere and strongest in the Arctic. Key Points: Decreased U.S. SO2 emissions lead to robust surface temperature increases over most northern hemisphere land surfaces Temperature responses in Asia and in the United States are similar in magnitude; Arctic responses are larger Aerosol optical depth (AOD) response and its relationship with radiative forcing vary strongly between models